2017
DOI: 10.1039/c7ta04695b
|View full text |Cite
|
Sign up to set email alerts
|

Template-engineered epitaxial BiVO4 photoanodes for efficient solar water splitting

Abstract: The photoelectrochemical properties of template-engineered epitaxial BiVO4 photoanodes have been enhanced approximately 10 times that of bare BiVO4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 42 publications
2
31
0
Order By: Relevance
“…Moreover, the volume fraction of BVO in the thin films decreased with the increase of the deposition temperature. In 2017, Song et al reported the growth of epitaxial BVO using a thin γ-WO 3 template layer deposited on a SrTiO 3 (001) (STO) substrate covered by a SrRuO 3 (SRO) bottom electrode using pulsed laser deposition [45]. γ-WO 3 , BVO, and BVO/γ-WO 3 were sequentially deposited in situ on the SRO/STO substrate at 550°C, a laser energy density of 2.0 J•cm −2 , and a repetition rate of 10 Hz.…”
Section: Pldmentioning
confidence: 99%
“…Moreover, the volume fraction of BVO in the thin films decreased with the increase of the deposition temperature. In 2017, Song et al reported the growth of epitaxial BVO using a thin γ-WO 3 template layer deposited on a SrTiO 3 (001) (STO) substrate covered by a SrRuO 3 (SRO) bottom electrode using pulsed laser deposition [45]. γ-WO 3 , BVO, and BVO/γ-WO 3 were sequentially deposited in situ on the SRO/STO substrate at 550°C, a laser energy density of 2.0 J•cm −2 , and a repetition rate of 10 Hz.…”
Section: Pldmentioning
confidence: 99%
“…As a result of such efforts, a few candidates have been introduced and investigated extensively. The promising candidates are BiVO 4 [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24], Fe 2 O 3 [25][26][27][28][29][30][31][32], and BiFeO 3 [33][34][35]. Figure 2 shows the band gap energies and band edge positions of various semiconductors with respect to the water redox potential.…”
Section: Absorption Of Solar Radiationmentioning
confidence: 99%
“…In general, the establishment of epitaxial thin film photoelectrode has been widely recognized to maximize the potential of photoelectrode materials in pursuit of a further breakthrough by exploring its fundamental properties. For that reason, recently, various research on the growth of the epitaxial BiVO 4 have been reported, to explore its fundamental properties for PEC water splitting [13,19,[56][57][58][59][60][61][62][63]. Based on many theoretical predictions, the research related to the growth of the epitaxial monoclinic BiVO 4 (a = 5.1956 Å, b = 5.0935 Å, c = 11.6972 Å, β = 90.387 • ) films have been focused on growth along the c-axis.…”
Section: Application Of Facet Engineering In Pec Water Splittingmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, there are many methods, which have been developed to prepare BiVO 4 photoelectrodes for use in solar water oxidation. The representative synthesis methods are (1) metal organic decomposition (MOD) combining with the spin coating or spray pyrolysis deposition [21][22][23], (2) electrophoretic deposition (EPD) and chemical bath deposition (CBD) [24][25][26][27], and (3) vacuum deposition methods such as sputtering deposition and pulsed laser deposition (PLD) [18][19][20][28][29]. The MOD is a facile method to synthesize BiVO 4 materials for photoelectrodes.…”
Section: Strategies To Enhance Photoelectrochemical Properties Of Bivomentioning
confidence: 99%